RNASeq-derived transcriptome comparisons reveal neuromodulatory deficiency in the CO(2) insensitive brown Norway rat - Puissant, Madeleine M (J Physiol, 2015)
Raphé-derived serotonin (5-HT) and thyrotropin-releasing hormone (TRH) play important roles in fundamental, homeostatic control systems such as breathing and specifically the ventilatory CO(2) chemoreflex. Brown Norway (BN) rats exhibit an inherent and severe ventilatory insensitivity to hypercapnia but also exhibit relatively normal ventilation at rest and during other conditions, similar to multiple genetic models of 5-HT system dysfunction in mice. Herein, we tested the hypothesis that the ventilatory insensitivity to hypercapnia in BN rats is due to altered raphé gene expression and the consequent deficiencies in raphé-derived neuromodulators such as TRH. Medullary raphé transcriptome comparisons revealed lower expression of multiple 5-HT neuron-specific genes in BN compared to control Dahl salt-sensitive rats, predictive of reduced central nervous system monoamines by bioinformatics analyses and confirmed by high-performance liquid chromatography measurements. In particular, raphé Trh mRNA and peptide levels were significantly reduced in BN rats, and injections of the stable TRH analogue Taltirelin (TAL) stimulated breathing dose-dependently, with greater effects in BN versus control Sprague–Dawley rats. Importantly, TAL also effectively normalized the ventilatory CO(2) chemoreflex in BN rats, but TAL did not affect CO(2) sensitivity in control Sprague–Dawley rats. These data establish a molecular basis of the neuromodulatory deficiency in BN rats, and further suggest an important functional role for TRH signalling in the mammalian CO(2) chemoreflex.